Walkability 101: A Multi-Method Assessment of the Walkability at a University Campus. (May 2020) - King, Sarah B.; Kaczynski, Andrew T.; Knight Wilt, Jacqueline; Stowe, Ellen W.
The aim of this study is to evaluate objective and perceived campus walkability as an environmental support for physical activity within a large Southeastern university. Ten university routes were evaluated twice for 24 key walkability characteristics. Eighty-three campus member surveys (62 students, 21 faculty/staff) were administered and assessed campus members' familiarity with walkability, attitudes about walking as a form of physical activity, and perceptions of whether specific elements of the campus layout encouraged physical activity. At least 90% of routes had sidewalks, curb cuts, and crosswalks. Likewise, over 85% of participants perceived the campus layout to encourage physical activity. Faculty/staff members were more familiar with the term walkability and considered walking as a form of physical activity than students ( p < .05). Both campus members' perceptions and environmental audits identified strengths and weaknesses for diverse walkability attributes. Results will be used to improve campus infrastructure and promote increased walking and physical activity at the university.